A STATISTICAL APPROACH TO DEVELOPMENT OF TASTE MASKED EFFERVESCENT TABLETS OF SILDENAFIL CITRATE CONTAINING KYRON T134 - OZA, NISHANT; SAGAR, SWATI; KHODAKIYA, AKRUTI; SAHU, ASIT (International Journal of Applied Pharmaceutics, 2020)
Objective: The aim of present work was to mask the bitter taste of sildenafil citrate by preparing drug resin complex (DRC) and develop sildenafil citrate 100 mg effervescent tablets. Methods: Sildenafil citrate and kyron T134 complexes were prepared at different conditions and evaluated for taste and drug loading. Optimized DRC was use to formulate the dispersible tablet by direct compression technique. A 32 full factorial design was use to study the effect of effervescent agent (X1) and croscarmellose sodium (X2) on dispersion time (Y1) and wetting time (Y2). Factorial batches were also evaluated for thickness, hardness, content uniformity, friability, in vitro drug release and stability studies. Multiple linear regression analysis, ANOVA and graphical representation of the influence factor by 3D plots were performing by using sigma plot 11.0. A Check point batch was design according to the results of desirability value and evaluated for all the parameter Results: FT-IR study confirm that sildenafil citrate and kyron T134 were compatible with each other. Among the various DRC batch B29 was found with less bitter and give a more drug loading. Checkpoint batch showed no significance difference between predicted value and actual value for dispersion time and wetting time and it was found stable during stability study. Conclusion: Sildenafil citrate bitter tast was masked by kyron T134 and full factorial design result was indicate that independent variables have significant effect on dependent variables